Personal data state monopoly loosing as a national security risk - Klimashin, Aleksandr G. (Journal of the Belarusian State University. Sociology, 2019)
It is obvious that in recent decades, the state structures of the vast majority of countries are headily losing the monopoly on citizens’ personal data. In the author’s view, this also poses a threat to the individual and to national security in general. The problem is caused by the fact that the development of Internet technologies increases the number of different service companies that provide information services: access to information data banks, Internet connection, applications for mobile devices and so on. When providing such services, most companies collect personal data and the need for such measures is not always obvious. However, we have come to a situation where many third-party companies have already collected a significant amount of information about citizens, the control of which is extremely difficult.